The incidence of musculoskeletal disorders and stakeholder perceptions of work challenges in South-Eastern Nigerian quarry mining industry - Egwuonwu, Victor Afamerfuna (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2020)
Musculoskeletal disorders (MSDs) are very common among industrial labourers, leading to sick leave absence, disability and low productivity at work. MSDs have multifactorial causes, thereby making it difficult to pinpoint the extent of the contributions of the various risks regarding the mechanism of its pathophysiology. Previously, attempts were made to study regional pain symptoms in varying occupational groups, disregarding the particularities of the different workplace situations. It is important to highlight, that quantifying physical exposure factors that contribute to MSDs occurrence using quantitative approach alone could be inadequate. It is therefore imperative to incorporate qualitative approach to unmask accompanying psychosocial stressors, which are mostly explanatory variables. The study investigated the following: 12-month retrospective prevalence of MSDs, prospective incidence, risk factors and pattern of MSDs in a 6-month follow-up survey of selected quarry mineworkers, who reported MSDs complaints at the mine clinic. The study also determined the level of psychosocial stress associated with working in the mine by understanding stakeholders' perception of work challenges, and how it influenced recurrence of MSDs. The study utilised a mixed method design with two phases: phase 1 was an initial baseline retrospective prevalence and a prospective cohort-control incidence survey. The Cultural and Psychosocial Influence on Disability (CUPID) questionnaire was translated into an Igbo-language version, cross-culturally adapted and utilized. The instrument was administered via oral interview and sought information on the following: demographic characteristics; pain in different anatomical sites and associated disability for tasks of daily living; as well as information on any change of job and reason during the study period, recent pain in different anatomical sites and associated disability for tasks of daily living; distress from common somatic symptoms; mental health status, sickness absence in the past 5-months for musculoskeletal pain. Phase 2 was a qualitative focus group discussion that engaged mine stakeholders on their perceptions of work challenges. Descriptive statistics of mean and standard deviation was utilised to analyse sociodemographic characteristics of participants. MSD incidence rates were estimated and the patterns of MSD incidence at different anatomical sites were also determined. The Cox proportional regression analyses were utilised to compare hazard ratios of MSD risks between the exposed cohorts and unexposed cohorts in the phase one incidence survey, alpha level was set at 0.05. Transcription, thematic and content analyses with the aid of Nvivo version 11 for windows was used to interpret stakeholders' perception of work challenges. The incidence of MSD was 6.2 per 1000, with shoulder pain being the most reported complaint (40% prevalence). This was followed by back pain with the distribution of back pain presented as follows: upper back (20.37%), lower back (45.50%) and both (34.13%). All participants reported previous medical history of back, shoulder and neck pain. The relative risk ratio of mineworkers to MSDs was 4.57, which implies that the mineworkers were approximately 5 times more at risk of developing MSDs compared to the recruited unexposed cohorts. Meanwhile, wrist pain (43.58%) was the highest MSD complaints which lead miners to be absent from work, followed by knee and back with 35.42% and 21% respectively. Physical job risks, such as III working underground and squatting or kneeling at work were all significantly associated with MSDs recurrence in all six body parts (HR: 1.12-1.92, 95%CI). Similarly, time pressure to complete task, low decision latitude, poor job satisfaction, somatisation and mental disorder, job insecurity, poor incentive system (HR: 1.01-1.75, 95%CI) were perceived by stakeholders' and participants alike in the study to be significantly associated with MSDs incidence. Quarrymen are exposed to high MSD risks associated with elevated psychosocial stress from their difficult work situations. The South Eastern Nigerian mine stakeholders believed that the high incidence of MSDs may have a substantial impact on health and productivity in the near future. Necessitating a clear need for the promotion of stakeholder's engagement concerning safe work policy implementation initiatives in the sector.
Keywords: Quarries and quarrying -- Health aspects -- Nigeria; Musculoskeletal system -- Diseases -- Nigeria; Miners -- Health and hygiene -- Nigeria